Estimating net child care price elasticities of partnered women with pre-school children using a discrete structural labour supply-child care model - Xiaodong Gong; Robert Breunig (The Australian Government, The Treasury, 2012)
The purpose of this paper is to improve our understanding of the relationship between child care price and women's labour supply. We specify and estimate a discrete, structural model of the joint household decision over women's labour supply and child care demand. Parents care about the well-being and development of their children and we capture this by including child care directly in household utility. Our model improves on previous papers in that we allow formal child care to be used for reasons other than freeing up time for mothers to work (such as child development) and we allow mothers' work hours to exceed formal child care hours. As informal and paternal care are important features of the data, this second relaxation of previous hour constraints is particularly important. We estimate the model using data from 2005 to 2007 from the Household Income and Labour Dynamics in Australia (HILDA) Survey. We find that on average a one percent increase in the net price of child care leads to a decrease in hours of labour provided by partnered women of 0.10 per cent and a decrease in the employment rate of 0.06 per cent. These estimates are statistically significant. Furthermore, we find that labour supply responses are larger for women with lower wages, less education, and lower income.
Keywords: C15; C35; J22; 330; Child care demand; child care price; women's labour supply; elasticities; discrete choice model